2006
DOI: 10.2215/cjn.00220605
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcomes of Acute Renal Failure in Hospitalized Patients

Abstract: The aim of this study was to provide a broad characterization of the epidemiology of acute renal failure (ARF) in the United States using national administrative data and describe its impact on hospital length of stay (LOS), patient disposition, and adverse outcomes. Using the 2001 National Hospital Discharge Survey, a nationally representative sample of discharges from nonfederal acute care hospitals in the United States, new cases of ARF were obtained from hospital discharge records coded according to the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
343
5
21

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 501 publications
(385 citation statements)
references
References 23 publications
16
343
5
21
Order By: Relevance
“…In this study, the most common underlying causes of ACD were infections, autoimmune inflammation, and malignancies; this is in line with data from hospitalised patients with ACD. 4,25,26 However, compared with the present study population, a markedly higher prevalence of renal insufficiency was reported among hospitalised patients with ACD. 3,25 This might be due to selection bias in the present study population; the transmural project separated renal anaemia as a distinct category of anemia, resulting in less renal insufficiency in this ACD patient group.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 74%
“…In this study, the most common underlying causes of ACD were infections, autoimmune inflammation, and malignancies; this is in line with data from hospitalised patients with ACD. 4,25,26 However, compared with the present study population, a markedly higher prevalence of renal insufficiency was reported among hospitalised patients with ACD. 3,25 This might be due to selection bias in the present study population; the transmural project separated renal anaemia as a distinct category of anemia, resulting in less renal insufficiency in this ACD patient group.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 74%
“…AKI refers to a clinical syndrome characterized by rapid decreases in renal function within a few hours to a few days, with accumulation of products of nitrogen metabolism such as creatinine and urea [10]. Causes of AKI vary from reduced kidney perfusion and prerenal azotemia to direct renal toxicity and postrenal obstruction, with AKI accounting for 1.9% of hospital inpatients [27]. Although increased serum creatinine and urea concentrations are the standard diagnostic laboratory criteria for AKI, they are relatively insensitive, becoming abnormal only when glomerular filtration rate decreases by more than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true with regards to acute kidney injury (AKI). AKI is a common entity in the hospital setting (1), even given the problems of definition and terminology that have recently received attention (2), and its causes are highly dependent on the population studied. Despite its enormous clinical impact, there have been few series of renal histology data published on the etiologies leading to AKI.…”
mentioning
confidence: 99%